Assessment of coconut bug, Pseudotheraptus wayi Brown (Hemiptera: Coreidae) damage on litchis in the Limpopo and Mpumalanga provinces of South Africa - Netshipise, Muano; Schoeman, Pieter Schalk; Gouws-Meyer, Reinette; Netshifhefhe, Shandukani Rudolf (African Entomology, 2025)
A survey of the coconut bug, Pseudotheraptus wayi damage on litchi fruits was conducted on eight farms in the Limpopo and Mpumalanga provinces to assess infestation levels. Ten Mauritius litchi trees per study site/farm were randomly selected and monitored in November and December 2023. Fallen/aborted immature fruits were collected from the mature litchi trees. A total of 11 083 fruits were collected and inspected for coconut bug damage. A total of 5 262 fruits were found to be damaged by coconut bugs. The results of the predicted percentage means from the GLMM modelling of the damage caused by the coconut bugs ranged from 19.71% to 62.41% on aborted fruit from farms, with 33.77% and 57.53% in Limpopo and Mpumalanga provinces, respectively. An indication that the coconut bug caused an average annual loss of 45.65% on immature fruit that were subsequently aborted in production from the two provinces. These findings point towards the fact that there is a considerable presence of coconut bug on the farms and also that litchi is a very good host of the coconut bug. The coconut bug damage increased when other host plants are cultivated in close proximity. Further research to evaluate economic impact of this pest is therefore needed.